Semiotic Studies: Cultivating Religious Characters in SDI: (Case Study in SDI KHA. Wahid Hasyim) - Rahma, Fatikh Inayahtur; Luqman, Luqman; Anggraini, Ade Eka (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2023)
Implementation of character education must be familiar from an early age, especially religious character. A religious character is a human character based on religious aspects. One example of religious character planting activities is the dhuha and istighosah prayers. Semiotics is interpreted as a description of ideas, objects, and situations related to media, messages, culture, and society. The purpose of this research is to find out the message of cultivating religious character in SDI KHA. Wahid Hasyim is based on signs (icons, indexes, and symbols). This study uses a qualitative research approach presented in a descriptive form and analyzed by studying Charles Sanders Pierce's semiotic theory with the triangle theory of meaning, namely Icons, Indexes, and Symbols. The results of this study are 1) SDI KHA. Wahid Hasyim, as one of the Nahdlatul Ulama-based schools, implemented a religious character outside of the learning process by habituating the Dhuha prayer in congregation and regular istighosah every Thursday. 2) Dhuha and istighosah prayer activities have messages and culture that want to be instilled and conveyed to students from an early age. 3) signs such as body posture, setting of the place, and time have their meaning related to the cultivation of religious character.